The Concept of Fairness In The Principle of Decency Reviewed From Business Ethics In Business Contracts - Sudargo Tandiono; Tanudjaja (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
Business agreements are often made only for the benefit of one party so that one party benefits and one party is harmed which only continues to put forward the principle of pacta sunt servanda. It is as if freedom in making a contract is final and absolute without anyone being able to intervene in the contract. This research has the basic purpose of reviewing business agreements judged by the implementation of business ethics as a reasonable consideration or not of a business agreement. The research method used in this study is a normative juridical method with a statute approach. Based on the results of existing research, the principle of propriety is closely related to the reasonableness of the contract agreement. Business agreements are basically formed not only based on consideration of legal provisions but also pay attention to business ethics. So business ethics can be applied as an indicator of the reasonableness of a business contract for the achievement of fairness.